Empowering Early Childhood Resilience: Development of Illustrated Storybooks for Disaster Mitigation with Local Wisdom - Efastri, Sean Marta; Novembli, Meta Silfia; Suharni, Suharni (FKIP Universitas Lampung, 2025)
Empowering Early Childhood Resilience: Development of Illustrated Storybooks for Disaster Mitigation with Local Wisdom. Objective: This study aimed to develop and evaluate the effectiveness of an illustrated storybook based on Tunjuk Ajar Melayu Riau as an innovative learning medium to enhance disaster preparedness in early childhood. Methods: The research adopted the Borg & Gall Research and Development (R&D) model. Study participants included 60 children aged 5-6 years across three PAUD sites in the Riau region, Indonesia. The intervention was conducted over two weeks with a total of six sessions. Effectiveness was assessed using the Disaster Preparedness Scale for Early Childhood (DPSEC) (12 items, α=0.87) through pre-test and post-test. Quantitative data were analyzed using the Paired-Sample T-test, Normalized Gain (N-Gain), and Cohen’s d Effect Size, complemented by qualitative thematic analysis of interviews. Findings: The book offers novelty by combining local cultural values with interactive features, such as a maze game, specifically designed to foster critical thinking and environmental awareness, addressing the current limitation of passive disaster education media in Indonesia. The effectiveness test results showed a highly significant increase in disaster preparedness scores, soaring from a pre-test mean of 55% to a post-test mean of 90% (t(59)=14.82, p<0.001). The impact was classified as high, with an average N-Gain of 0.71 and a strong Effect Size (d=1.92). Qualitatively, the Cultural Resonance of the Malay characters significantly boosted engagement, while the Maze Game mechanistically stimulated planning and critical thinking. Teachers rated the product as highly practical with an average score of 88%, confirming its feasibility and curricular alignment. Conclusion: The illustrated storybook based on Tunjuk Ajar Melayu Riau is an effective, feasible, and practical learning model for enhancing early childhood disaster preparedness. Its success is driven by the synergy between the maze's cognitive scaffolding and the contextual reinforcement of local wisdom, offering a vital model for culturally-based disaster mitigation education in Indonesia. However, generalization is currently limited to the Riau context. Keywords: cultural identity; disaster mitigation; early childhood education; tunjuk ajar melayu.